2020
DOI: 10.3892/etm.2020.8408
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of miR‑181a in patients with neonatal sepsis and its regulatory role in the lipopolysaccharide‑induced inflammatory response

Abstract: Neonatal sepsis (NS) poses a serious threat to the health of neonates worldwide. The present study aimed to investigate the diagnostic value of microRNA (miR)-181a in patients with NS and the regulatory role of miR-181a in lipopolysaccharide (LPS)-induced inflammation. A total of 102 neonates with NS and 50 neonates without sepsis were enrolled in the present study. The serum levels of miR-181a were estimated using reverse transcription-quantitative PCR. Receiver operating characteristic (ROC) analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Ji et al found that Sch B could increase miR-17-5p expression, promote in ammation, and decrease TLR4 expression in sepsis mice and LPS-induced macrophages [29]. The interaction between miR-141 and TLR4 3'-UTR was analyzed by luciferase reporter assay.The results show that TLR4 is the target gene of miR-141.miR-141 plays a role in neonatal sepsis by binding to the 3'-UTR region of TLR4.The mechanism of action of miR-181a in sepsis also con rms this view [30].The results of this study uncover the potential role of miR-141 as a useful potential therapeutic agent in the treatment of sepsisand provide a basis for the application of miR-141 in neonatal sepsis.However, the speci c mechanism of action of miR-141 in neonatal sepsis needs further investigation In short, the abnormal expression of miR-141 is related to the in ammatory response of neonatal sepsis, and miR-141 has a higher diagnostic accuracy in neonatal sepsis.The expression level of miR-141 in LPStreated cells was signi cantly inhibited.It was found that overexpression of miR-141 inhibited LPSinduced in ammation by targeting TLR4 in monocytes.Therefore, increasing the level of miR-141 may be alleviate neonatal sepsis.miR-141 is expected to become a potential diagnostic biomarker and therapeutic target in neonatal sepsis.…”
mentioning
confidence: 58%
“…Ji et al found that Sch B could increase miR-17-5p expression, promote in ammation, and decrease TLR4 expression in sepsis mice and LPS-induced macrophages [29]. The interaction between miR-141 and TLR4 3'-UTR was analyzed by luciferase reporter assay.The results show that TLR4 is the target gene of miR-141.miR-141 plays a role in neonatal sepsis by binding to the 3'-UTR region of TLR4.The mechanism of action of miR-181a in sepsis also con rms this view [30].The results of this study uncover the potential role of miR-141 as a useful potential therapeutic agent in the treatment of sepsisand provide a basis for the application of miR-141 in neonatal sepsis.However, the speci c mechanism of action of miR-141 in neonatal sepsis needs further investigation In short, the abnormal expression of miR-141 is related to the in ammatory response of neonatal sepsis, and miR-141 has a higher diagnostic accuracy in neonatal sepsis.The expression level of miR-141 in LPStreated cells was signi cantly inhibited.It was found that overexpression of miR-141 inhibited LPSinduced in ammation by targeting TLR4 in monocytes.Therefore, increasing the level of miR-141 may be alleviate neonatal sepsis.miR-141 is expected to become a potential diagnostic biomarker and therapeutic target in neonatal sepsis.…”
mentioning
confidence: 58%
“…Risk of bias is mainly derived from the index test. The conduct or interpretation of the index test introduced high risk in 6 records [ 7 , 8 , 17 , 19 , 23 , 28 ] and unclear risk in 13 articles [ 6 , 14 – 16 , 18 , 20 , 21 , 25 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accurate diagnosis is the first and most important prerequisite for the efficient treatment of diseases. To improve the treatment of infectious diseases in neonates, it is of value to distinguish cases of NS from neonates with pneumonia/respiratory tract infection ( 30 ). CRP and PCT were established as biomarkers for NS and are widely used for this purpose, but elevated CRP and PCT may also be detected in certain infectious and inflammatory diseases other than NS, such as pneumonia ( 31 ) and respiratory tract infection ( 32 ); thus, their application specificity is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 39 ) suggested that the circulating levels of miR-23b were decreased in patients with sepsis and were able to inhibit the LPS-induced inflammatory response in monocytes. Overexpression of miR-181a inhibited the LPS-induced inflammatory response at least partially by targeting Toll-like receptor 4( 30 ). The present study determined that the expression of miR-1184 was also downregulated in LPS-induced monocytes and overexpression of miR-1184 reversed the promoting effect of LPS on the inflammatory response in monocytes.…”
Section: Discussionmentioning
confidence: 99%